Development Of The Staffing System In Hotels In The Digital Economy: Economic And Legal Aspects - Yurievna Nikolskaya, Elena; Vladimirovna Pasko, Olga; Iosifovna Kovaleva, Natalia; Georgievna Fedorchukova, Svetlana; Ivanovna Novolodskaya, Galina (Opción, 2019)
The article is devoted to the analysis of economic and legal aspects of the development of staffing systems in hotels in the conditions of the digital economy. It has been established that a high-quality system of hotel educa- tion should meet the needs for the preparation and professional training of future hotel employees. It has been determined that the hotel staffing system is under formation and requires concerted efforts to ensure that levels of training of new specialists comply with hotels’ needs. It has been proven that the scientific substantiation of hotel staffing can be presented by such indicators as the state of the hotel industry’s hu-man potential, the determi- nation of development prospects of hotels at federal and regional levels. It has been determined that for the more efficient interaction of the parties in- volved in the training and re-training of hotel staff it is necessary to impose a legal duty on a person to constantly improve his/her professional knowl- edge and business skills, and to execute labor relations via a supplementary agreement.